DINAMIKA KELEMBAGAAN PENGELOLAAN AIR IRIGASI - BENNY RACHMAN; KETUT KARIYASA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2002)
The increasing demand of water for economic activities trigger a consequence of higherpressure of irrigation water needs. On the other side, Water User’s Association (P3A), anorganization managing irrigation water from tertiary and quarter channel up to the rice field,finds it difficult to manage water resource in perspective of quantity, times and place. In linewith that, institutional adjustment in both government institution and institution at farm levelshould be carried out in order to improve efficiency of water management. Furthermore, tosupport local autonomy and the empowerment of Water Users Assosiation to undertake largerresponsibility in irrigation management as a strategic approach to improve efficiency ofirrigation system management at the local level. The involvement of farmers in managingirrigation water distribution should be promoted up to the upper level, i.e. through thedevelopment of P3A federation based on hidrological spread i.e. irrigation area.